WORD WALL TECHNIQUE: A SOLUTION FOR TEACHING ENGLISH VOCABULARY - TEGUH DARMA KESUMA; M. HAVID FEBRIANSYAH (JETA (Journal of English Teaching and Applied Linguistic), 2023)
This scientific article discusses slang as a medium of adolescent communication in social interactions between others. The role of language becomes very important in every facet of human life. This article was written with the aim of providing information that slang has become a medium or communication tool for adolescents, also explaining about something that has to do with language as a means of communication in every human social interaction. In writing this article using the literature review method, all data is obtained from relevant literature data. In the discussion of this article explains about slang as a medium of communication among teenagers. The characteristics of slang in the form of words, acronyms and abbreviations, factors that influence the emergence and use of slang as a medium of communication, also explain the impact of the use of slang in social interaction. As social creatures, of course, humans need communication in their lives in order to establish relationships between others. From the writing of this article, it can be seen that the millennial generation or teenagers already have creativity in communicating, both through abbreviations and acronyms in the form of Indonesian and English, so that it can show the context of communication culture in the modern and cool world of teenagers.